Trichoderma sp. Antagonist Test Ability as an Inhibitor of Yellow Rot Disease Pathogens of Red Dragon Fruit Plants: (Hylocereus polyrhizus) - Elrisa Ramadhani; Kabul Warsito; Indra Irawan; Nur Ikhsan (International Journal of Science and Mathematics Education, 2024)
Dragon fruit plants originating from Central and South America have not been widely cultivated. This plant has only been cultivated intensively in several countries such as: Israel, Colombia, Nicaragua, Vietnam, Thailand, China and Australia. Macroscopic identification showed that the fungi associated with dragon fruit stems had similarities to the colony form of Colletotrichum gloeosporioides sp. Trichoderma is known to have antagonistic abilities against pathogenic fungi. Trichoderma is easily found in soil ecosystems and plant roots. The method in this study is a survey method. Determination of the sample using purposive sampling or Judgmental sampling method, namely purposive sampling is a sampling method that selects objects (vines) that are considered attacked or have symptoms of pathogen attack. Trichoderma sp is also tolerant to stress and able to inactivate pathogenic microbial enzymes. In addition, Trichoderma sp. Able to produce enzymes that hydrolyze pathogenic cell walls which will inhibit the synthesis of pathogenic cell walls and increase their fungicidal activity, as a result of which pathogenic fungi experience a decrease in growth rate.